Colorectal Cancer-Associated Immune Exhaustion Involves T and B Lymphocytes and Conventional NK Cells and Correlates With a Shorter Overall Survival - Sorrentino, Carlo; D’Antonio, Luigi; Fieni, Cristiano; Ciummo, Stefania Livia; Di Carlo, Emma (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is one of the most common cancer worldwide, with a growing impact on public health and clinical management. Immunotherapy has shown promise in the treatment of advanced cancers, but needs to be improved for CRC, since only a limited fraction of patients is eligible for treatment, and most of them develop resistance due to progressive immune-exhaustion. Here, we identify the transcriptional, molecular, and cellular traits of the immune-exhaustion associated with CRC and determine their relationships with the patient’s clinic-pathological profile. Bioinformatic analyses of RNA-sequencing data of 594 CRCs from TCGA-PanCancer collection, revealed that, in the wide range of immune-exhaustion genes, those coding for PD-L1, LAG3 and T-bet were associated (Cramér's V=0.3) with MSI/dMMR tumors and with a shorter overall-survival (log-rank test: p=0.0004, p=0.0014 and p=0.0043, respectively), whereas high levels of expression of EOMES, TRAF1, PD-L1, FCRL4, BTLA and SIGLEC6 were associated with a shorter overall-survival (log-rank test: p=0.0003, p=0.0188, p=0.0004, p=0.0303 and p=0.0033, respectively), independently from the molecular subtype of CRC. Expression levels of PD-L1, PD-1, LAG3, EOMES, T-bet, and TIGIT were significantly correlated with each other and associated with genes coding for CD4+ and CD8+CD3+T cell-markers and NKp46+CD94+EOMES+T-bet+ cell markers (OR >1.5, p<0.05), which identify conventional(c)NK cells. Expression of TRAF1 and BTLA co-occurred with both T cell-markers, CD3g, CD3d, CD3e, CD4, and B cell-markers, CD19, CD20 and CD79a (OR>2, p<0.05). Expression of TGFb1 was associated only with CD4+ and CD8+CD3e+T cell-markers (odds-ratio>2, p<0.05). Expression of PD-L2 and IDO1 was associated (OR>1.5, p<0.05) only with cNK cell-markers, whereas expression of FCRL4, SIGLEC2 and SIGLEC6 was associated (OR>2.5; p<0.05) with CD19+CD20+CD79a+B cell markers. Morphometric examination of immunostained CRC tissue-sections, obtained from a validation-cohort of 53 CRC patients, substantiated the biostatistical findings, showing that the highest percentage of immune-exhaustion gene expressing cells were found in tumors from short-term survivors and that functional exhaustion is not confined to T lymphocytes, but also involves B cells, and cNK cells. This study provides novel insight into the immune-exhaustion landscape of CRC and emphasizes the need for a customized multi-targeted therapeutic approach to overcome resistance to current immunotherapy.